Deficits in narrative abilities in child British Sign Language users with specific language impairment. Issue 3 (12th March 2014) - Herman, Ros; Rowley, Katherine; Mason, Kathryn; Morgan, Gary
Abstract This study details the first ever investigation of narrative skills in a group of 17 deaf signing children who have been diagnosed with disorders in their British Sign Language development compared with a control group of 17 deaf child signers matched for age, gender, education, quantity, and quality of language exposure and non‐verbal intelligence. Children were asked to generate a narrative based on events in a language free video. Narratives were analysed for global structure, information content and local level grammatical devices, especially verb morphology. The language‐impaired group produced shorter, less structured and grammatically simpler narratives than controls, with verb morphology particularly impaired. Despite major differences in how sign and spoken languages are articulated, narrative is shown to be a reliable marker of language impairment across the modality boundaries.